Hypothesis Statement and Statistical Testing: A Tutorial - K Sharma, Narendra (BOHR International Journal of Operations Management Research and Practices, 2023)
Many researchers and beginners in social research have several dilemmas and confusion in their minds aboutthe hypothesis statement and statistical testing of hypotheses. A distinction between the research hypothesis andstatistical hypotheses and understanding the limitations of the historically used null hypothesis statistical testingis useful in clarifying these doubts. This article presents some data from the published research articles to supportthe view that theisformat as well as thewillformat is appropriate to stating hypotheses. The article that presentsa social research framework to present the research hypothesis and statistical hypotheses in a proper perspective.